Fixed Points in complete 2-Metric Spaces of Orbitally Continuous Mappings - Prof . Abdullah Khalifa Saeed Ali (Aljameai, 2026)
Abstract                                                                                                                                                               This paper examines a collection of fixed-point theorems for orbitally continuous mappings in the setting of complete 2-metric spaces. Through the analysis of these mappings under various conditions, we establish results regarding the existence and uniqueness of fixed points.Also, we provide further related results that emphasize the structural characteristics of 2-metric spaces within the framework of orbital continuity.                                                                       المستخلص :                                                                            تتناول هذه الورقة مجموعة من مبرهنات النقطة الثابتة للتطبيقات المستمرة مدارياً ضمن إطار الفضاءات ذات المترية الثنائية    الكاملة. ومن خلال تحليل هذه التطبيقات تحت مجموعة متنوعة من الشروط، نستخلص نتائج تتعلق بوجود ووحدانية النقاط الثابتة. وايضا ، نقدم نتائج أخرى ذات صلة تُبرز الخصائص البنيوية للفضاءات ذات المترية الثنائية في سياق الاستمرارية المدارية.